Taxonomy and Ecology of Marine Algae (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The term “algae” refers to a large diversity of unrelated phylogenetic entities, ranging from picoplanktonic cells to macroalgal kelps. Marine algae are an important primary producer in the marine food chain, responsible for the high primary production of coastal areas, providing food resources in situ for many grazing species of gastropods, peracarid crustaceans, sea urchins or fish. Recent findings indicate that marine environments have rapidly changed due to global warming over the past several decades. This change has led to significant variations in marine algal ecology. For example, a long-term increase in ocean temperatures due to global warming has facilitated the intensification of harmful algal blooms, which adversely impact public health, aquatic organisms, and aquaculture industries. Thus, extensive studies have been conducted, but there is still a gap in our understanding of the variation in their ecology in accordance with future marine environmental changes. To fill this gap, studies on the taxonomy and ecology of marine algae are highly necessary. We have invited algologists to submit research articles that enable us to advance our understanding of the taxonomy and ecology of marine algae. Fourteen papers have been collected so far, which cover different aspects of the taxonomy and ecology of marine algae, including understudied species, interspecific comparisons, and new techniques.